Clinical Features in 36 Patients Homozygous for the ARG 506 → GLN Factor V Mutation - Emmerich, Joseph; Alhenc-Gelas, Martine; Aillaud, Marie-Françoise; Juhan-Vague, Irène; Jude, Brigitte; Garcin, Jean-Marie; Dreyfus, Marie; de, Moerloose Philippe; Le Querrec, Agnès; Priollet, Pascal; Berruyer, Micheline; Vallantin, Xavier; Wolf, Martine; Aiach, Martine; Fiessinger, Jean-Noël (Thrombosis and Haemostasis, 1997)
We analyzed the clinical features of 36 patients homozygous for the Arg 506 to Gin factor V mutation and found a circumstantial event at risk for thrombosis in 29 of the 31 patients with thrombosis. The most frequent predisposing factors were the post-partum period and the use of oral contraceptives in women, and surgery in both sexes. Venous thrombosis recurred in 48% of the patients. One patient had a myocardial infarction at age 33 years, and also had an antiphospholipid syndrome. Homozygous Gin 506 mutation leads to far less severe thrombotic complications than homozygous protein C and protein S deficiencies and does not seem to predispose patients to arterial thrombosis.